PERAN SERTA MASYARAKAT DALAM PENGEMBANGAN WAE REBO SEBAGAI SEBUAH DESTINASI PARIWISATA BERBASIS MASYARAKAT DI NUSA TENGGARA TIMUR - Yefri Yunikson; I Wayan Pantiyasa (Jurnal Ilmiah Hospitality Management, 2017)
Wae Rebo is a unique traditional village, known as a famous cone shape house architecture. In Manggarai language, the house is known as Mbaru Niang, it has been discovered in 1920. Mbaru Niang has seven buildings with the different names; they are Niang Gendang, Niang Gena Mandok, Niang Gena Jekong, Niang Gena Ndorom, Niang Gena Jintam, and Niang Gena Maro. They were built in sphere around an altar with the circle shape, called Compang. The people of Wae Rebo considered Compang as a sacred thing. Wae Rebo also has another kinds of culture like Penti ceremony and Caci dance. Not only rich of the cultures, but they also rich of rich potentials of nature such as range of mountain forest, and various kinds of birds like Gagak Flores (Corvusflorensis) and Celepuk Flores (Otusalfredi). They are known as the endemic species of Flores Island. Community Based Tourism (CBT) is a tourism concept used in Wae Rebo tourism development. CBT concept in Wae Rebo tourism was applied from the beginning like planning, implementation, and controlling done by society. To protect the culture, people of Wae Rebo insisted a society organization named Cultural Conservation Institute of Wae Rebo and supported by social organization. The motto of the Cultural Conservation Institute is â€œMohe Wae Reboâ€ means â€œPreserve Wae Reboâ€.